The influence of service responsiveness, employee competence and the use of technology on the satisfaction of business actors through service quality at the Karimun Regency Investment and one-stop integrated service office - Mardalena Mardalena; Fachrudin Fachrudin; Mohamad Gita Indrawan (Review of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study aims to analyze the influence of service responsiveness, employee competence, and use of technology on business actor satisfaction through service quality at the DPMPTSP Karimun Regency. In the current era of digitalization, improving the quality of public services is one of the priorities for meeting the expectations of business actors in interacting with government institutions. Research Methodology: This study uses a quantitative approach with a survey method of 162 business actors who use the services of the Karimun Regency Investment and One Stop Integrated Services Service. Data were collected using a questionnaire distributed through Google Forms. Results: The results of the analysis show that service responsiveness has a positive and insignificant effect on service quality with an effect of 11.9%. Employee competency and the use of technology have a positive effect on service quality, with an effect of 58.8% and 26.5%, respectively. Service responsiveness had a negative and insignificant effect on business actor satisfaction, with an effect of 09.8%. Employee competency and the use of technology on business actor satisfaction have a positive and significant effect on business actor satisfaction, with an influence of 34.2% and 18.3%, respectively. Service quality had a positive effect on business actor satisfaction, with an influence of 55.3%. Service Responsiveness has a positive and insignificant effect on Business Actor Satisfaction through Service Quality, with an influence of 06.6%. Employee Competency had a positive and significant effect on Business Actor Satisfaction through Service Quality, with an influence of 32.4%. The use of technology had a positive and significant effect on Business Actor Satisfaction through Service Quality, with an influence of 14.7%. Good service quality acts as a mediator in the relationship between service responsiveness, employee competence, and the use of technology, and business satisfaction. Thus, improving service quality is key to increasing the satisfaction of business actors in the DPMPTSP Karimun Regency. Recommendation: This research underlines the importance of increasing employee competency through continuous training and adopting the latest technology to create more responsive and efficient services.